Peripartal disease and reproductive function in high-yielding dairy cows - Noor Syaheera Ibrahim
The aim of the first study was to determine whether early postpartum disease, or yield level and age predict reproductive success in terms of conception, or other reproductive parameters such as timing, duration or maximum of the first luteal phase, in dairy cows.In this industry, we hypothesized that early postpartum disease will have an effect on reproductive parameters and age/yield factors.Two Scottish dairy farms were used for the studies, cows on Farm A are medium-yielding and milked 2 times/day, and cows on Farm B are hihg-yielding and milked 3 times/day.Results from Farm A showed no overall effect of disease on reproductive parameters (p>0.05), and if anything, more cows grouped as "Disease" tended to be in the early conception category (p=0.07).However, early postpartum disease reduced the production of Farm B's high-yielding cows in the first and second month of lactation, and it affected luteal phase parameters with significant reductions in progestrone (p>0.05), as well as reproductive success, with fewer cows bred after estrus and more being culled (p<0.05). In the second study the pattern of postpartum resumption of ovulatory cycles was determined in Farm A and B cows by using progestrone and estradiol analysis in milk together with herd management information, starting at 14 days postpartum (pp).We hypothesized that more Disease cows would have the abnormal resumption pattern postpartum, while more Control cows had normal pattern.For this study a normal resumption pattern was defined as cows having a normal cycle,a heat or Al record and/or clear E2 peak before 6- days pp.Again,on Farm A postpartum disease, or other cow factors, did not appear to affect the proportion of cows with normal or abnormal resumption patterns. However, on Farm B, cows with a normal resumption pattern had or tended to have, better fertility (shorter intervals to Al and to conception), and fewer Disease cows turned out to have a normal resumption pattern (p<0.05), with a short first ovulatory cycle being linked to a pp ketosis diagnosis.When analyzing cows according to whether they ovulated late (after 28 Days in Milk, DIM) or early pp,results showed that there is no benefit to early ovulation, as it does not lead to an earlier conception and late ovulating cows had a characteristic snapshot sequence of luteal function and cycles between weeks 4 and 7 pp related to earlier conception.The third study determined milk metobolites in milk samples from Control and Disease cows from 14DIM using a metabolimics analysis.In the case the Disease cows included only those with a ketosis diagnosis (although half of these also had Metritis diagnose), because the previous study revealed that fertelity was affected in ketosis and ketosis+ uterine disease cows,showing short cycles in the first luteal phase, conceiving late or being culled.Thirteen cows (7 Control and 6 Disease) were employed and one single milk samples were collected for metabolomics analysis.From 466 milk metabolites, a list of 120 metabolites was extracted for further analyses, which revealed 6 clear candidates changed between Control and Disease cows and related to glycolysis and ketosis.Specifically, Itaconate, 3-Phospho-D-glycerate and Phosphoenolpyruvate are derived from the glycolysis metabolism,while Hydroxybutyrylcarnitine, (R)-3-Hydroxybutanoate and O-Butanoylcarnitine are part of ketogenesis.Such metabolites could become future biomarkers of the continued effects of severe NEB pp, and perhaps explain some of the dysfunction leading to diminished reproductive success in high-yielding dairy cows.